2006
DOI: 10.1097/01.wnr.0000224773.66904.e7
|View full text |Cite
|
Sign up to set email alerts
|

Low alpha-synuclein 126 mRNA levels in dementia with Lewy bodies and Alzheimer disease

Abstract: Alpha-synuclein, a main component of Lewy bodies in synucleinopathies and senile plaques in Alzheimer disease, is centrally involved in neurodegeneration. Three different isoforms (alpha-synuclein 112, 126, and 140) resulting from alternative splicing have been described so far. The present study explores alpha-synuclein 126 mRNA expression levels in the prefrontal cortex of six patients with dementia with Lewy bodies, eight patients with Lewy body variant of Alzheimer disease, eight patients with Alzheimer di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Though accelerated fibrillogenesis and enhanced aggregation was expected with the deletion of the functional domains [10,29], the alternative isoforms actually aggregate less than the canonical isoform SNCA140 [12]. The interruption of the domain responsible for protein-membrane interaction at the protein N-terminus even makes SNCA 126 an aggregation-preventing isoform [28]. In this way, we surmise that transcripts SNCA-007 and SNCA-E3E4, which correlated positively with the monoaminergic neuron function, were neuron protective isoforms.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Though accelerated fibrillogenesis and enhanced aggregation was expected with the deletion of the functional domains [10,29], the alternative isoforms actually aggregate less than the canonical isoform SNCA140 [12]. The interruption of the domain responsible for protein-membrane interaction at the protein N-terminus even makes SNCA 126 an aggregation-preventing isoform [28]. In this way, we surmise that transcripts SNCA-007 and SNCA-E3E4, which correlated positively with the monoaminergic neuron function, were neuron protective isoforms.…”
mentioning
confidence: 69%
“…In line with previous reports indicating presynaptic α-synuclein aggregation is involved in synaptic function [25], the current study showed a significant positive correlation between α-synuclein transcripts and cerebral 18 F-AV133 SUVRs. While the biological and pathological significance of the different α-synuclein splicing variants remains unknown, these isoforms have been associated with intracellular aggregations [26][27][28][29]. Though accelerated fibrillogenesis and enhanced aggregation was expected with the deletion of the functional domains [10,29], the alternative isoforms actually aggregate less than the canonical isoform SNCA140 [12].…”
mentioning
confidence: 99%
“…Part of our present data underline these results showing the drastic diminution of all SNCB transcripts in the cortex of G-pDLB. Noteworthy, that the same samples are also characterized by the overexpression of aggregation-prone isoforms SNCA112 and SNCA98, accompanied by the reduction of the whole transcript SNCA140, and the potentially protective isoform SNCA126 [10,12,13]. Taken together, there is a decrease in the expression of all SNCB isoforms, SNCA140 and protective SNCA126, but an increase in the expression of both aggregation-prone SNCA isoforms.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, it has been reported that the accumulation of small presynaptic AS aggregates correlates with dendritic spine loss causing neurodegeneration in DLB [9]. So far, four different splice variants of the AS gene (SNCA) have been described [10], and alterations in their differential expression could represent one of the molecular mechanisms leading to AS oligomerization and aggregation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent discoveries highlight that alternative splicing of α-syn may also play a crucial role in the mechanisms mediating PD [28][31]. So far, deletion of exon 3 [126-Syn] or exon 5 [112-Syn] or both exon 3 and 5 [98-Syn] have been identified [32], [33].…”
Section: Introductionmentioning
confidence: 99%